A density functional theory study of van der Waals interaction in carbon nanotubes. Issue 3 (13th March 2023) - Wang, Houng‐Wei; Hayashi, Michitoshi
Abstract: In this article, we investigate the effect of van der Waals force in zigzag carbon nanotubes (CNTs) including single‐wall CNT (SWCNT) and double‐walled CNT (DWCNT) structures with several interaction configurations. The solid‐state density functional theory is employed to calculate the geometric optimization, normal mode frequencies, and IR and Raman spectra with the periodic boundary condition. For SWCNTs, we find that the Raman intensity is not affected by the tube diameter or the electronic structure. The IR absorption, however, increases with the tube diameter. We find that the close metallicity of the electronic structure has a significant impact on the IR simulations. When the van der Waals force is applied outside the CNTs at a distance longer than 3.0, the effect on Raman spectra is minimal but some effects can still be confirmed by IR absorption. When the van der Waals force acts inside the CNTs, the effect on the spectrum can be observed, especially at a distance of 2.8 Å, both IR and Raman can be significantly enhanced in many modes. Abstract : The effect of van der Waals force in zigzag double‐walled carbon nanotubes (DWCNTs) by using solid‐state density functional theory to simulate the IR and Raman spectra.